Uji Total Flavonoid dan Aktivitas Antioksidan Fraksi Aktif Kulit Kayu Manis (Cinnamomi burmannii cortex) sebagai Diabetic Ulcer - Anggi Septya Insan; Novitaria Br Sembiring; Nerly Juli Pranita Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2026)
Diabetes mellitus is a chronic disease that can cause complications, one of which is diabetic ulcer, a wound that is difficult to heal due to increased oxidative stress. The use of natural ingredients such as cinnamon bark (Cinnamomi burmannii cortex), which is rich in flavonoids and phenolic compounds, has the potential to be an alternative supportive therapy due to its antioxidant activity. This research seeks to identify overall flavonoid levels and antioxidant properties within cinnamon bark active fractions while assessing its effectiveness for healing diabetic ulcers. The investigation involved laboratory experiments utilizing specific extraction techniques. Primary processing employed the maceration approach using 70% ethanol solvent, which was subsequently followed by a secondary liquid-liquid separation procedure to isolate desired chemical compounds. Total flavonoid amounts underwent analysis through AlCl3 colorimetry with UV-Vis spectrophotometry, while free radical scavenging capacity was evaluated employing DPPH methods and documented as IC50 values. The study revealed the ethyl acetate fraction contained peak flavonoid percentages (0.8637%) and exhibited the most effective antioxidant strength IC50 12.2716 ppm). These data imply that ethyl acetate extracts from cinnamon bark offer substantial viability for development as supplementary medicinal agents for diabetic ulcer care by effectively neutralizing oxidative damage during healing.